2022
DOI: 10.2147/ijwh.s367953
|View full text |Cite
|
Sign up to set email alerts
|

Economic Evaluations of HPV Vaccination in Targeted Regions of Low- and Middle-Income Countries: A Systematic Review of Modelling Studies

Abstract: Background:In countries with limited resources, a targeted HPV vaccination strategy by focusing in selected regions is preferable to be implemented than a nationwide vaccination strategy.Objective: This study aimed to review articles on economic evaluations of HPV vaccination in countries over the world that applied targeted vaccination strategies. Methods: Approximately 1769 articles were obtained from two databases (1242 and 527 articles from PubMed and ProQuest, respectively). The inclusion criteria in this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…As Kenya transitions from Gavi support, relevant stakeholders may need to assess the best strategy between continuing with the current product and adopting options that could provide similar or greater health benefits at lower net costs. The estimated percent reduction in cervical cancer deaths (42-60 % reduction) compares with a systematic review of modelling studies in low-and middle-income countries (LMICs) by Frianto et al, which estimated reduction of cervical cancers by HPV vaccination at 20-72 % and showed that HPV vaccination could be cost-saving in several instances [44]. Most HPV vaccination economic evaluation studies have demonstrated costeffectiveness for different implementation strategies.…”
Section: Tablementioning
confidence: 85%
“…As Kenya transitions from Gavi support, relevant stakeholders may need to assess the best strategy between continuing with the current product and adopting options that could provide similar or greater health benefits at lower net costs. The estimated percent reduction in cervical cancer deaths (42-60 % reduction) compares with a systematic review of modelling studies in low-and middle-income countries (LMICs) by Frianto et al, which estimated reduction of cervical cancers by HPV vaccination at 20-72 % and showed that HPV vaccination could be cost-saving in several instances [44]. Most HPV vaccination economic evaluation studies have demonstrated costeffectiveness for different implementation strategies.…”
Section: Tablementioning
confidence: 85%
“… 26 , 56 Many LMICs have implemented school-based HPV vaccination programs, which have seen relatively high HPV vaccination rates with great potential for sustainability and scalability particularly in primary schools. 7 , 13 , 68–71 School-based delivery strategies on average had higher coverage and performed better than facility-based programs and the majority (90%) of LMIC vaccination campaigns utilized school-based or a mix of school and facility-based programs. 56 Integrating the HPV vaccine into other school-based health services and other community outreach services for adolescents not enrolled in school may further decrease delivery cost and increase vaccine coverage.…”
Section: Resultsmentioning
confidence: 99%
“…Clinical interventions in LMICs have found that vaccinating against HPV can reduce cervical cancer cases by 50% to 75%. 7 Every five-year delay in HPV vaccine roll-out contributes to 2 million cervical cancer deaths. 8 The HPV vaccine needs to be given promptly to adolescents as the vaccine is most effective against HPV-related disease outcomes when given at younger ages.…”
Section: Introductionmentioning
confidence: 99%
“…This highlights significant disparities caused by the limited availability of national the human papillomavirus (HPV) vaccine, cervical screening, and treatment programmes, as well as social and economic factors that influence health outcomes. Cervical cancer is a result of a long-lasting infection with HPV, and the implementation of prophylactic HPV vaccination and conducting screening and treatment for pre-cancerous lesions are highly successful [2] and economically efficient methods for preventing cervical cancer [3,4]. Vaccination not only provides protection to individuals who receive the vaccine against specific HPV types, but it can also decrease the occurrence of these targeted types in the general population.…”
Section: Introductionmentioning
confidence: 99%